2013
DOI: 10.7567/jjap.52.08jh07
|View full text |Cite
|
Sign up to set email alerts
|

Blue Superluminescent Light-Emitting Diodes with Output Power above 100 mW for Picoprojection

Abstract: We present a blue InGaN research and development superluminescent light-emitting diode (SLED) that is suitable for picoprojection. The SLED reaches an output power of >100 mW with a peak wavelength of 443 nm and a spectral bandwidth of >2.6 nm as well as a single-mode far-field driven in cw mode at 25 °C. In order to figure out an optimized waveguide design, which enables such a high output power at lowest operation current, we compare the performance of diodes with curved and tilted shaped ridges in det… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
24
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(24 citation statements)
references
References 20 publications
0
24
0
Order By: Relevance
“…In parallel, highly directional beam (limited etendue) with high power, low speckle noise and droop-free can be achieved [19]. Conventionally, SLD is used in optical coherence tomography (OCT) [20], fiber gyroscope [21], sensing [22], and picoprojections [23]. Our previous works reported the fabrication of semipolar InGaN-based SLDs and the potential for white light generation with a CRI of 68.9 [19] and for data communications [24,25] However, the limited availability and high-cost of semipolar GaN substrate present significant challenges in eventual foundry adoption.…”
Section: Introductionmentioning
confidence: 99%
“…In parallel, highly directional beam (limited etendue) with high power, low speckle noise and droop-free can be achieved [19]. Conventionally, SLD is used in optical coherence tomography (OCT) [20], fiber gyroscope [21], sensing [22], and picoprojections [23]. Our previous works reported the fabrication of semipolar InGaN-based SLDs and the potential for white light generation with a CRI of 68.9 [19] and for data communications [24,25] However, the limited availability and high-cost of semipolar GaN substrate present significant challenges in eventual foundry adoption.…”
Section: Introductionmentioning
confidence: 99%
“…Table 1 summarizes the design and performance of the demonstrated GaN-based SLDs, comparing the emission wavelength, substrate material, configuration, waveguide design, and the maximum light output power reported in each case. 405 nm c-GaN "j-shape" waveguide curved ridge 350 mW (cw) [24] 408 nm c-GaN "j-shape" waveguide "j-shape" ridge 200 mW (cw) [25] 410 ~ 445 nm c-GaN tilted waveguide 2 µm ridge 30 ~ 55 mW (cw) [26] 420 nm c-GaN tilted facet 2 µm ridge 2 mW (cw) 100 mW (pulse) [27] 420 nm c-GaN "j-shape" waveguide AR/HR coating 3 µm ridge 200 mW (cw) [28] 439 nm m-GaN facet roughening 4 µm ridge 5 mW (pulse) [29] 443 nm c-GaN curved waveguide 2 µm ridge 100 mW (cw) [30] 445 nm c-GaN oblique facet 5 µm ridge - [31] 447 nm Semipolar GaN passive absorber 7.5 µm ridge 256 mW (cw) [17] 500 nm c-GaN curved waveguide 2 µm ridge 4 mW (pulse) [32] Since most of InGaN/GaN QW SLDs are grown on a polar, c-plane GaN substrate, there is a growing interest to develop high efficient violet-blue SLDs on nonpolar or semipolar substrates owing to a reduced polarization field presented in the QW structure [2]. Studies on semipolar and nonpolar GaN-based LEDs and LDs have revealed that the enhanced electron and hole wavefunction overlap is expected for InGaN/GaN QWs grown on nonpolar (m-plane) and semipolar GaN substrates, leading to an enhanced internal quantum efficiency [2,3].…”
Section: Introductionmentioning
confidence: 99%
“…In the quest for ever-increasing output powers, high reflectivity (HR) coatings have been applied to the rear facets of several reported SLEDs [14]. The HR coating is designed to reflect almost all backward propagating light, which then undergoes another pass through the waveguide before ideally being coupled out of the device.…”
Section: Introductionmentioning
confidence: 99%